The Mediating Role of Motivation in Relationship Between Compensation and Leadership on Employee Performance - Hasanah, Annur Wahyu; Suyono, Joko; Elisabeth, Damarsari Ratnasahara (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The purpose of this study is to analyze the effect of compensation and leadership on employee performance, and also to analyze the mediating role of motivation.. Design/methodology/approach: The population in this study were 63 employes of Textile Industries in Surabaya, East Java, Indonesia. Questionnaire was used to obtain the data and data analysis technique used was Partial Least Square (PLS). Findings: The results indicated that compensation and leadership affect employee performance, either directly or indirectly. motivation is able to mediate the effect of compensation and leadership on employee performance. Research limitations/implications: This research is limited to doing in Textile Industries in East Java, Indonesia. For generalization so that further research can be carried out in different organizations or companies and in different regions (cities). Practical implications: The results of this research can be used as a reference to employee performance in textile industries and similar industries. Originality/value: The results of the research show that among the variables of compensation, leadership and motivation need to be implemented in textile industries and similar industries. Paper type: This paper can be categorized as research paper.